Thunderclap headache as an initial manifestation of acute aortic dissection: a case report and review of literature - Ranjeevan, Mario; Nielsen, Valeriia; Stenager, Egon; Mamoei, Sepehr (Frontiers in Cardiovascular Medicine, 2025)
The authors describe the case of a 54-year-old man with sudden onset severe headache accompanied by transitory sensory-motor deficits in all extremities, and mild abdominal pain as the initial manifestation of acute aortic dissection. Despite clinical symptoms mimicking subarachnoid hemorrhage and transitory cerebral ischemia, CT-angiography of the cerebrum and thorax revealed a Stanford type A aortic dissection. Consequently, the patient underwent insertion of a prosthesis at the aortic root and arch. In this case report, we suggest a high level of suspicion for aortic dissection in patients presenting with a sudden severe headache and/or neurological deficits accompanied by chest/back/abdominal pain, nausea, and loss of consciousness. At the same time, asymmetry of pulse and blood pressure asymmetry of the arms should also raise suspicion. An acute CT angiography with the aim of timely diagnosis will allow earlier treatment for this life-threatening condition.